2001
DOI: 10.1046/j.0960-7439.2001.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth size and morphology in twins

Abstract: The remarkable similarity in the tooth size and morphology of monozygotic twins suggests a strong inheritability factor to tooth size and shape and that these may be useful as additional tools for zygosity determination along with other dental traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 8 publications
(8 reference statements)
0
40
0
2
Order By: Relevance
“…A similar study on occlusal surface morphology has been performed on the occlusal surface of nine pairs of permanent molars [Kabban et al, 2001]. Three pairs were from MZ twins, four pairs from DZ twins and two from unrelated controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study on occlusal surface morphology has been performed on the occlusal surface of nine pairs of permanent molars [Kabban et al, 2001]. Three pairs were from MZ twins, four pairs from DZ twins and two from unrelated controls.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 34 pairs of twins, it was shown that the mesiodistal dimension for all permanent teeth in MZ twins was more concordant than in DZ twins [Kabban et al, 2001]. Studies by Townsend and collaborators indicated a high phenotypic variation of intercuspal distance with moderate genetic influence [Townsend et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La morphologie des surfaces occlusales serait fortement sous influence génétique [23,58,59], la similarité de taille et de contours, analysée par informatique et traitement statistique, montrant une nette différence dans la comparaison de jumeaux MZ avec des jumeaux DZ et des sujets non apparentés [21]. Certaines particularités anatomiques (tubercule de Carabelli, taurodontisme, talon cingulaire) ou des anomalies morphologiques (gemination, fusion, dens in dente, dent conoïde.…”
Section: Anomalies De Morphologieunclassified
“…With surface form (shape) measurements, Co-ordinate Measuring Machines (CMMs) are more suited for the inspection of automotive parts in industry since the 1950's (Bosch, 1995). Since the late 90's, along with the development of new technology in optics and computing, numerous applications have been advanced in the fields of medicine and dentistry (Chadwick, 1989;Seymour et al 1996;Kabban, et al 2001;Zou, et al , 2009Cherukara GP et al 2002;Theocharopoulos et al, 2010;Morris et al 2011 ).…”
Section: Proposed Alternativementioning
confidence: 99%